1991
DOI: 10.1126/science.1903559
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Tuning of Pigments Underlying Red-Green Color Vision

Abstract: Variations in the absorption spectra of cone photopigments over the spectral range of about 530 to 562 nanometers are a principal cause of individual differences in human color vision and of differences in color vision within and across other primates. To study the molecular basis of these variations, nucleotide sequences were determined for eight primate photopigment genes. The spectral peaks of the pigments specified by these genes spanned the range from 530 to 562 nanometers. Comparisons of the deduced amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
298
4
8

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 465 publications
(322 citation statements)
references
References 14 publications
12
298
4
8
Order By: Relevance
“…The same sites also account for the spectral shift between the red and green LWS pigments of primates ( Neitz et al 1991;Ibbotson et al 1992;Williams et al 1992) and are also substituted in the duplicated LWS genes of the blind cave fish, Astyanax ( Yokoyama & Yokoyama 1990). These are all examples of convergent evolution in distantly related species and confirm the assertion (Hunt et al 2001(Hunt et al , 2004) that in many cases spectral tuning of a visual pigment can only be achieved by substitution at a limited number of sites that are able to interact with the chromophore to achieve the spectral shift and maintain a fully functional pigment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same sites also account for the spectral shift between the red and green LWS pigments of primates ( Neitz et al 1991;Ibbotson et al 1992;Williams et al 1992) and are also substituted in the duplicated LWS genes of the blind cave fish, Astyanax ( Yokoyama & Yokoyama 1990). These are all examples of convergent evolution in distantly related species and confirm the assertion (Hunt et al 2001(Hunt et al , 2004) that in many cases spectral tuning of a visual pigment can only be achieved by substitution at a limited number of sites that are able to interact with the chromophore to achieve the spectral shift and maintain a fully functional pigment.…”
Section: Discussionmentioning
confidence: 99%
“…A duplicated LWS opsin gene underlies the red and green pigments in Old World primates (Dulai et al 1999) and the spectral shifts between these two pigments are largely attributable to substitutions at three sites, 180, 277 and 285, with polar residues Thr, Tyr and Thr, respectively, occupying these sites in the red pigment compared with non-polar residues Ala, Phe and Ala, respectively, in the green pigment ( Neitz et al 1991;Ibbotson et al 1992). Significantly, the honey possum and the fat-tailed dunnart also differ at sites 277 and 285, with polar Tyr and Thr in the more LW-shifted honey possum pigment.…”
Section: Resultsmentioning
confidence: 99%
“…The clear variations in the pigments of the New World monkeys suggested it would be profitable to correlate spectral positioning with sequence differences among several different phenotypic versions of the M and L cone pigments in these animals. Accordingly, we made sequence comparisons for a total of eight different opsin genes, six from two species of New World monkey and two from human dichromats (44). The results indicated that as few as three amino acid substitutions were sufficient to explain the variations in the spectra of these pigments.…”
Section: Cone Photopigment Polymorphismmentioning
confidence: 99%
“…In contrast, the NPXXY region is highly homologous among cone pigments and rhodopsin (data not shown). The only difference in the chromophore-binding site between green and red pigments is in the immediate vicinity of retinal, where Phe 261 is replaced by Tyr 261 (red), as predicted from studies on the spectral tuning of primates aimed at understanding the molecular properties underlying red-green color vision (155,156). These studies were extended to identify residues responsible in in vitro experiments [157, 158; reviewed in (159)].…”
Section: Cone Visual Pigmentsmentioning
confidence: 99%